Non-vitamin K antagonist oral anticoagulants and warfarin in atrial fibrillation patients with concomitant peripheral artery disease. Issue 1 (28th November 2019) - Lee, Hsin-Fu; See, Lai-Chu; Li, Pei-Ru; Liu, Jia-Rou; Chao, Tze-Fan; Chang, Shang-Hung; Wu, Lung-Sheng; Yeh, Yung-Hsin; Kuo, Chi-Tai; Chan, Yi-Hsin; Lip, Gregory Y H
Abstract: Aims : To investigate the effectiveness, safety, and outcomes of lower limb events for non-vitamin K antagonist oral anticoagulants (NOACs) vs. warfarin among atrial fibrillation (AF) patients with concomitant peripheral artery disease (PAD). Methods and results: In this nationwide retrospective cohort study collected from Taiwan National Health Insurance Research Database, a total of 5768 and 2034 consecutive AF patients with PAD patients taking NOACs or warfarin were identified from 1 June 2012 to 31 December 2017, respectively. We used propensity score stabilized weighting to balance covariates across study groups. In the cohort, there were 89% patients were taking low-dose NOAC (dabigatran 110 mg twice daily, rivaroxaban 10–15 mg daily, apixaban 2.5 mg twice daily, or edoxaban 30 mg daily). Non-vitamin K antagonist oral anticoagulant was associated with a comparable risk of ischaemic stroke, and a lower risk of acute myocardial infarction [hazard ratio (HR): 0.61, 95% confidence interval (CI): 0.42–0.87; P = 0.007], lower extremity thromboembolism (HR: 0.56, 95% CI: 0.44–0.72; P < 0.0001), revascularization procedure (HR: 0.58, 95% CI: 0.47–0.72; P < 0.0001), lower limb amputation (HR: 0.32, 95% CI: 0.23–0.46; P < 0.0001), and all major bleeding (HR: 0.64, 95% CI: 0.50–0.80; P = 0.0001) than warfarin after weighting. The advantage of NOACs over warfarin persisted in high-risk subgroups including patients of ≥75 years of age, diabetes, renal impairment, or use of concomitant antiplatelet agent. Conclusion : This population-based study indicated that NOACs were associated with a comparable risk of ischaemic stroke, and a significantly lower risk of major adverse limb events and major bleeding than warfarin among AF patients with concomitant PAD. Therefore, thromboprophylaxis with NOACs may be considered for such patients.